AN OPTIMAL CONTROL ON THE DYNAMICS OF WILDEBEEST, ZEBRA AND LION PREY PREDATOR INTERACTIONS IN SERENGETI ECOSYSTEM. (2022) - CHARLES, RAYMOND; ∗, ∗; MAKINDE, OLUWOLE DANIEL; KUNG'ARO, MONICA
No abstract available